Semen quality and diversity of morphological sperm abnormalities in bulls: breed and strain effects - M. A. Kleshchev; V. L. Petukhov; L. V. Osadchuk (Вавиловский журнал генетики и селекции)
At present great attention is paid to studying genetic regulation of farm animal adaptations to environmental conditions. This problem is very important due to a wide expansion of highly productive cattle breeds created in Europe and North America. However, until the present no investigation of changing semen quality in bulls of imported breeds during their adaptations to environmental conditions of Western Siberia has been conducted. The aim of this study was to investigate semen quality peculiarities and the diversity of morphological sperm abnormalities in bulls of imported and local breeds kept in the environmental conditions of the southern part of Western Siberia. We determined sperm concentration, sperm count, and rate of sperm with progressive motility and percentage of morphologically normal spermatozoa. The rate of sperm abnormalities according to Blome’s classifcation was determined too. It was found that the mean values of sperm concentration, sperm motility and percentage of morphologically normal spermatozoa in the bulls investigated were similar to those in bulls kept in European countries. Interbreed diﬀerences in these parameters were not found. However, bulls of the Red Danish, Angler, and Simmental breeds had a higher percentage of misshapen sperm head and pyriform sperm head than bulls of the BlackWhite breed. An interstrain diﬀerence in sperm motility in bulls of the BlackWhite breed was observed. It was found that bulls of Reﬂection Sovereign 198998 strain had lover sperm motility than bulls of Wis Burke Ideal 1013415 strain. No interstrain diﬀerences in sperm production, percentage of morphologically normal spermatozoa and rate of main sperm abnormalities were found. Thus, it has been found that the environmental conditions of the southern part of Western Siberia do not seriously aﬀect the sperm production, sperm motility or percentage of morphologically normal spermatozoa in bulls. However, the increased rate of misshapen and pyriform sperm heads in the bulls of the foreign breeds points to a need to study sperm DNA fragmentation.